2017
DOI: 10.1002/polb.24287
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal elastomer actuators: Synthesis, alignment, and applications

Abstract: Liquid crystal elastomers (LCEs) are a unique class of materials which combine rubber elasticity with the orientational order of liquid crystals. This combination can lead to materials with unique properties such as thermal actuation, anisotropic swelling, and soft elasticity. As such, LCEs are a promising class of materials for applications requiring stimulus response. These unique features and the recent developments of the LCE chemistry and processing will be discussed in this review. First, we emphasize se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
237
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(237 citation statements)
references
References 147 publications
(243 reference statements)
0
237
0
Order By: Relevance
“…[5] Liquid crystalline network (LCN) actuators are typically fabricated by firstly orienting the mesogens through mechanical stretching or surface alignment, and subsequently locking the ordered structure through a chain cross-linking reaction. [6] Upon reversible order-disorder phase transition of the mesogens, LCNs can exhibit macroscopic and reversible shape change. Although substantial progress has been made in the development of LCN actuators in terms of actuation performance in the past decade, [7] their large-scale applications are still hampered by the demanding actuator fabrication and the lack of processability.…”
mentioning
confidence: 99%
“…[5] Liquid crystalline network (LCN) actuators are typically fabricated by firstly orienting the mesogens through mechanical stretching or surface alignment, and subsequently locking the ordered structure through a chain cross-linking reaction. [6] Upon reversible order-disorder phase transition of the mesogens, LCNs can exhibit macroscopic and reversible shape change. Although substantial progress has been made in the development of LCN actuators in terms of actuation performance in the past decade, [7] their large-scale applications are still hampered by the demanding actuator fabrication and the lack of processability.…”
mentioning
confidence: 99%
“…LCs, due to their mesoscale ordering and fluidic properties, have been shown to be useful in the templated synthesis of polymeric materials . Past studies have shown multiple routes toward the synthesis of polymeric materials using liquid crystalline environments.…”
Section: Methodsmentioning
confidence: 99%
“…Since the chirality, within a size range that spans from molecular sizes to meso-and macroscopic sizes, is an important phenomenon that plays a significant role in determining the behavior, [26][27][28] application, [12,29,30] and performance [31,32] of the nanoscopic to microscopic objects; control over the synthesis of objects with such symmetries provides significant contribution to their use in certain applications.LCs, due to their mesoscale ordering and fluidic properties, have been shown to be useful in the templated synthesis of polymeric materials. [33][34][35][36] Past studies have shown multiple routes toward the synthesis of polymeric materials using liquid crystalline environments. The route for the synthesis of liquid crystal elastomer microparticles involves the polymerization of single component or multicomponent mixtures of reactive mesogens with mono-or diacrylate reactive groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many other synthetic approaches for LCE preparation have been described and reviewed elsewhere . However, mentioning the above‐selected examples will help the understanding of the versatility of these materials and how it is possible to manipulate their synthesis to achieve different LCE properties and structures towards possible applications in biology.…”
Section: Preparation Methods and Smart Properties Of Lcesmentioning
confidence: 99%